Polyaniline/Polystyrene Blends: In-Depth Analysis of the Effect of Sulfonic Acid Dopant Concentration on AC Conductivity Using Broadband Dielectric Spectroscopy - Noora Al-Thani; Mohammad K. Hassan; Jolly Bhadra (International Journal of Polymer Science)
This work presents an in-depth analysis of the alternating current (AC) conductivity of polyaniline-polystyrene (PANI-PS) blends doped with camphor sulfonic acid (CSA) and prepared using an in situ dispersion polymerization technique. We prepared the blends using fixed ratios of PS to PANI while varying the concentration of the CSA dopant. The AC conductivity of the blends was investigated using broadband dielectric spectroscopy. Increasing CSA resulted in a decrease in the AC conductivity of the blends. This behaviour was explained in terms of the availability of a lone pair of electrons of the NH groups in the polyaniline, which are typically attacked by the electron-withdrawing sulfonic acid groups of CSA. The conductivity is discussed in terms of changes in the dielectric permittivity storage (ε′), loss (ε′′), and modulus (M′′) of the blends over a wide range of temperatures. This is linked to the glass transition temperature of the PANI. Dielectric spectra at low frequencies indicated the presence of pronounced Maxwell-Wagner-Sillars (MWS) interfacial polarization, especially in samples with a low concentration of CSA. Electrical conduction activation energies for the blends were also calculated using the temperature dependence of the direct current (DC) conductivity at a low frequency (σdc), which exhibit an Arrhenius behaviour with respect to temperature. Scanning electron microscopy revealed a fibrous morphology for the pure PANI, while the blends showed agglomeration with increasing CSA concentrations.